Jovens na reforma agrária: perspectiva intergeracional e lógicas de sucessão no assentamento Novo Horizonte - Campos dos Goytacazes – RJ - Siqueira Cordeiro, Manuela Souza (Universidade Federal Rural do Rio de Janeiro, 2015)
The main goal of this paper is to verify the young settler's expectations and representations, regarding the land succession of the Land Reform public policy. The succession is one of the crucial moments to family agriculture, when are negotiated the collective orientations and the individual interests of the young people. The Land Reform context brings some considerations that must be in the analysis, once the land might still be in the process of definitive titling. In this way, the settled family does not have yet the property title, what probably might influence in its appropriation. Furthermore, the land extension can be considered small to the social reproduction of the young settlers' new domestic units. In this sense, there will be analyzed the material heritages (the access to land propriety) as well as the immaterial heritages (the qualities associated to work, access to education and to formal employment) of the young settler in a way to achieve an intergerational perspective in the succession analysis in the Novo Horizonte settlement.